Size miniaturization of chipless RFID tag using metamaterial structure - Mohd Ezwan B. Jalil; Mohamad Kamal A. Rahim; Osman B. Ayop; Noor Asmawati Samsuri (Institute of Advanced Engineering and Science, 2019)
A Chipless RFID based Modified Complementary Split Ring Resonator (MCSRR) with Different Width (DW) which is metamaterial structure is designed using PET substrate ( =3, loss tangent = 0.025 at 2 GHz) to miniaturize effective length size of conventional split ring resonator. The MCSRR structure with DW provides less size about 17% compared with the conventional MCSRR structure. The single MCSRR resonator with different width only requires a frequency range of 12 % of Complementary Split Ring Resonator (CSRR) resonator. The slotted MCSRR resonator is located underneath substrate and within substrate is connected with transmission lines. The insertion loss value of MCSRR resonator is used to encode ID information of chipless RFID with maximizing ID information using Frequency Position technique. The best swapping parameter for encoding ID number information is split gap of both ring compare with other parameter such as spacing between ring and width of ring.